English as Lingua Franca in Starbucks Workspace: A Systematic Literature Review - Rama Sultan Akbar; Sandrella Salsabila; Raditya Septian Fajar Nugroho (Universitas Duta Bangsa Surakarta, 2025)
This study explores the role of English as a Lingua Franca (ELF) within the Starbucks workspace, emphasizing its function in facilitating global communication across the company's diverse international branches. By employing a Systematic Literature Review (SLR) method, this research synthesizes findings from various scholarly articles, case studies, and organizational reports to examine how ELF shapes communication practices, team dynamics, and corporate culture in a transnational corporate setting. The review identifies key themes such as language policy, intercultural competence, power dynamics, and communication efficiency in multinational workspaces. Results indicate that ELF serves not only as a practical communication tool but also as a strategic asset that enables Starbucks to maintain consistency in brand identity, training, and operational coordination worldwide. The study contributes to the understanding of ELF in globalized corporate environments and offers insights for language policy planning in other multinational corporations seeking to enhance communication across linguistic and cultural boundaries.